Ministry of the Interior Decree No. 2596 of the Year 2023 Amending Certain Provisions of Ministerial Decree No. 1777 of the Year 2023 On the Rules, Procedures, and Controls of Enforcing Prime Minister’s Decree No. 3326 of the year 2023 = وزارة الداخلية قرار رقم 2596 لسنة 2023 بتعديل بعض أحكام القرار الوزارى رقم 1777 لسنة 2023 فى شأن قواعد وإجراءات وضوابط تنفيذ قرار رئيس مجلس الوزراء رقم 3326 لسنة 2023 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic